Inquiring Sport and Physical Activity students’ perceptions using metaphors as research tools (Investigar las percepciones de los estudiantes de Deporte y Actividad Física utilizando metáforas como instrumento de investigación) - María Ángeles Martínez Ruiz; María Alejandra Ávalos Ramos; Gladys Merma Molina (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this research is to analyse the metaphorical expressions designed by Science of Sport and Physical Activity university students of first academic year, as a tool of inquiring two research questions: on the one hand, their perceptions of their physical education teachers, and the other hand, the meaning physical activity has in students’ personal life. 51 students from the University of Alicante have participated in the study. Qualitative data analysis software AQUAD 7 was used for data processing. The results obtained from the analysis of the metaphors designed by students showed that their view of physical education teachers was very positive. The findings also indicate that sport and physical activity were considered to be essential and a source of emotional and physical health. The conclusions also highlighted that students don’t strengthen the social dimension of physical activity, and that it could be imperative to foster a more collaborative learning.